Distortion of the ecocracy principle in the job creation law: A humanistic legal critique of national environmental protection and management - Affifah Fatma Dewi; Nazilaturrohmah Fatmi Fadhila (Universitas Negeri Yogyakarta, 2025)
The concept of green at the constitutional level is basically a commitment to the environment. This concept is part of an ideology that places man's relationship with nature. The concept of green is not a status, verb or adjective, but a process. Environmental awareness is very important in order to continue to protect and preserve the environment. This study aims to analyze The concept of ecocracy in the context of the 1945 Constitution and its Regulations in Indonesia and the implementation of the concept of ecocracy in Law Number 6 of 2023 concerning the Determination of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation into Law in the Protection and Management Cluster Environment. This research uses normative research methods with a normative juridical approach. The idea of ecocracy must be a guideline in making state policy, political law in Indonesia, so that the ideal to continue to preserve the environment can be achieved. In order to be executed in the state system, the concept of ecocracy must be translated into a green constitution and green legislation. The establishment of the Job Creation Perppu which has later been enacted into Law Number 6 of 2023 is considered to override many aspects of environmental sustainability and the Law contains simplification of permits, disorientation of strict liability, and restrictions on environmental rights.